Cold Compresses As An Intervention To Reduce Post Tonsillectomy Pain Intensity - Christina Yuliastuti; Siti Aminah; Nur Muji Astuti; Imroatul Farida (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction:Tonsillectomy is the most common procedure performed to treat tonsillitis. One of the clinical manifestations of this procedure is pain which occurs mediator released during surgery stimulates pain nerve endings, so pain management is necessary. Objectives: The aims of this study to analyzed cold compresses to reduce pain intensity in post-tonsillectomy patients Methods: This research design was used a pre experiment with a one group pre test post test design approach, that conducted for months. July -August 2024, involving 17 post-operative patients in Room H2 RSPAL dr. Ramelan Surabaya, using purposive sampling. Data were analyzed using Friedman Test. Results: The results showed that in the first 3 hours after tonsillectomy, the intensity of pain which was in range of 5-7 (median 6) decreased to 3-5 (median 3) after being given cold compress therapy for 10-15 minutes, with a p-value of 0.001 which indicated that this decrease is statistically significant. 3 hours after first intervention, pain intensity decreased again to 1-4 (median 3) after being given cold compress therapy, with a p-value (0.001). Conclusions: This indicates that cold compresses are effective in reducing pain consistently at different times after surgery. The use of cold compresses as a non-pharmacological pain management method may be considered as part of the post-operative care protocol